Relational conflicts experienced through digital platforms among generation z sorority women - Frankenberger, William R. (Kansas State University, 2024)
The purpose of this phenomenological study was to explore the lived experiences of relational conflict among female Generation Z sorority members inflicted through digital platforms and how those women attempted to resolve digital conflicts. The study included 9 sorority women participants between the ages of 18-22. Grounded in social constructivism, this phenomenological qualitative inquiry findings were gleaned from two participant interactions including a 60-minute, semi-structured interviews via Zoom, and a second interview elicitation process to review their lived example of a digital conflict. Using the interpretative phenomenological analysis (IPA) process, the findings from interviews were coded first by experiential statements and exploratory notes followed by a cross analysis of each individual case, producing four group experiential themes (GETs). Findings related to the first research question were found within three of the four GETs which included: conflict initiation and escalation, digital dynamics, and relational influences coupled with societal effects. Findings related to the second research question were gleaned within the final GET and included women and conflict, various conflict styles and their use among participants, and finally, the resolution considerations and strategies attempted. The findings of the study supported use of digital communication and also suggested that an aim of digital conflict is to engage in a more destructive and hurtful discourse given that without the existence of a relationship, resolution is not actively sought or desired. Findings also suggest a reimaging of the conflict lexicon to reflect the digital landscape. Suggestions for future research included focusing further our comprehension of digital conflicts within broader contexts including cross-cultural perspectives and an exploration into policy development and enforcement regarding digital conflicts on college campuses. The significance of this study provides beginning research on a topic that is rarely explored while also contributing to the research showing how relationships, especially among women, impact digital conflicts given the unique dynamics that are present in a digital medium compared to face-to-face mediums.
Keywords: Relational conflict; Digital conflict; Sorority; Social media; Group communication; Cyberbullying